Filsafat Pendidikan Islam dan Pengembangan Karakter Peserta Didik - Diva Vania Evelyna; Isna Asyifah Ramadani; Rofingatun Nazilah (Balai Teknologi dan Komunikasi Pendidikan DIY, 2026)
This paper outlines the contribution of Islamic educational philosophy to the development of students’ character in the midst of changing times, particularly in the context of digitalization, globalization, and the post-truth phenomenon. Islamic educational philosophy is understood as a framework for thinking that emphasizes a balance between the development of intellectual, spiritual, moral, and social aspects, grounded in the principle of tawhid. This study aims to investigate the essence of Islamic educational philosophy, the concept of students from an Islamic perspective, and its relationship to character building. The methodology employed is a literature review, analyzing various sources related to Islamic educational philosophy and character education. The findings of this study indicate that Islamic education focuses not only on academic achievement but also on the formation of good character through the integration of values of faith, exemplary behavior, and the cultivation of habits in daily life. Students are viewed as individuals possessing innate potential (fitrah) that must be comprehensively developed toward becoming a complete human being (insan kamil). The discussion also emphasized that character development in Islamic education must be supported by a solid philosophical foundation, the vital roles of teachers and parents, and teaching strategies that are responsive to technological advancements. In the post-truth era, the primary challenges are the decline in critical thinking skills and the proliferation of misinformation; therefore, character education must be strengthened through digital literacy and moral literacy. Thus, the philosophy of Islamic education is highly relevant in addressing the challenges of globalization. Through the integration of the values of tawhid, akhlak, and knowledge, Islamic education is expected to produce a generation that is not only intellectually intelligent but also possesses strong character, noble morals, and the ability to adapt wisely to modern life. Keywords: philosophy of Islamic education, character, ethics, students, post-truth, globalization.